CFTR dysfunction leads to defective bacterial eradication on cystic fibrosis airways - Wu, Min; Chen, Jeng-Haur (Frontiers in Physiology, 2024)
Dysfunction of the cystic fibrosis transmembrane conductance regulator (CFTR) anion channel by genetic mutations causes the inherited disease cystic fibrosis (CF). CF lung disease that involves multiple disorders of epithelial function likely results from loss of CFTR function as an anion channel conducting chloride and bicarbonate ions and its function as a cellular regulator modulating the activity of membrane and cytosol proteins. In the absence of CFTR activity, abundant mucus accumulation, bacterial infection and inflammation characterize CF airways, in which inflammation-associated tissue remodeling and damage gradually destroys the lung. Deciphering the link between CFTR dysfunction and bacterial infection in CF airways may reveal the pathogenesis of CF lung disease and guide the development of new treatments. Research efforts towards this goal, including high salt, low volume, airway surface liquid acidosis and abnormal mucus hypotheses are critically reviewed.